2021
DOI: 10.1021/acs.analchem.1c01397
|View full text |Cite
|
Sign up to set email alerts
|

Direct Electrochemical Determination of Peroxide-Type Explosives Using Well-Dispersed Multi-Walled Carbon Nanotubes/Polyethyleneimine-Modified Glassy Carbon Electrodes

Abstract: The sensitive and selective determination of peroxide-based explosives (PBEs) in the field/on site is an important analytical challenge. Most methods claiming to detect PBEs are indirect, actually detecting their decomposition product, H2O2. Here, we present an electrochemical sensor for direct detection of organic peroxide explosives, that is, triacetone triperoxide (TATP) and hexamethylenetriperoxide diamine (HMTD), using well-dispersed multiwalled carbon nanotubes/polyethyleneimine (MWCNTs/PEI)-modified gla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…The same interaction applies to HMTD as their structures are very similar to each other and contain peroxide bonds just like TATP. The important advantages of the proposed voltammetric method are that the sensor electrode can measure the analytes at neutral pH (instead of high pH values reported by other authors, questioning analyte stability) and that the environment in which electrochemical measurements are made contains high water (80 % by volume) [33].…”
Section: Voltammetric Approaches For the Detection Of Explosivesmentioning
confidence: 98%
See 1 more Smart Citation
“…The same interaction applies to HMTD as their structures are very similar to each other and contain peroxide bonds just like TATP. The important advantages of the proposed voltammetric method are that the sensor electrode can measure the analytes at neutral pH (instead of high pH values reported by other authors, questioning analyte stability) and that the environment in which electrochemical measurements are made contains high water (80 % by volume) [33].…”
Section: Voltammetric Approaches For the Detection Of Explosivesmentioning
confidence: 98%
“…In other words, the voltammograms showed that the GCE modified with pristine MWCNTs provided a better performance than GCE modified with acid-functionalized MWCNTs and unmodified GCE [32]. In another study by Arman et al (2021), the well-dispersed MWCNTs in PEI solution were used for the modification of the GC electrode to prepare a new sensor electrode to enable direct and precise determination of TATP and HMTD. TATP molecules were kept in the polymer matrix as a consequence of the intermolecular interaction of polyelectrolyte molecules with the amine groups.…”
Section: Carbon Nanotubesmentioning
confidence: 99%
“…The direct electrochemical reduction of TATP and HMTD was carried out using the DPV method in an 80/20% (v/v) H 2 O–acetone solvent medium within the concentration range of 10–200 mg L –1 for TATP and 25–200 mg L –1 for HMTD, and the detection limits were 1.5 mg L –1 and 3.0 mg L –1 , respectively. Additionally, common ions, different types of energetic materials such as nitro-aromatic and nitramine-type explosives, and electroactive camouflage materials did not interfere with the proposed method …”
mentioning
confidence: 99%
“…Additionally, common ions, different types of energetic materials such as nitro-aromatic and nitramine-type explosives, and electroactive camouflage materials did not interfere with the proposed method. 27 In this study, we prepared peroxide-based energetics memory-polycarbazole (PCz) films decorated with gold nanoparticles (AuNPs) for direct, sensitive, and selective determination of TATP and HMTD by the DPV method using cathodic peak current measurement. These sensor electrodes were prepared in two steps.…”
mentioning
confidence: 99%
See 1 more Smart Citation